(3GdJegjOGJs - (3Sja GdOjf GdCeOj (B: (3CHh GdMSf Ydj Hf CHi Ydj Hf eMeOs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3BNQgG (B:s
(3TQM GdETGQI Edi GdEjLGH hGdSdH s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B7 - (3U (B205 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs